Giant frontal mucopyocele: Draft III approach - Veloso-Teles, Rafaela (2014)
Mucoceles are mucous-filled cystic lesions of the paranasal sinuses that can result in bone erosion with extracranial, intracranial or orbital extension. They are denominated mucopyocele if there is infection of the mucous filling. The surgical approach when they are localized in the frontal sinus is a challenge for the ENT surgeon; some authors prefer exclusively endoscopic techniques that go from marsupialization to Draf III procedures, while others advocate combined osteoplastic approaches. We report a case of 74 year-old man who presented at our hospital center (CHAA) outpatient clinic with right frontal tumefaction with 10 month evolution and slow growing. After imagiological study, it was established the diagnosis of a giant frontal mucocele. The patient was submitted to endoscopic sinus surgery, through a Draf type III frontal sinusotomy, without any complications. After one-year follow-up, there were no symptoms or clinical, endoscopic or imagiological signs of mucocele recurrence.